Islamic Education Curriculum Development - Try Masriah; Wafik Ajizah; Mahwiyah (Penerbit Hellow Pustaka, 2023)
The Islamic education curriculum is materials in the form of activities, knowledge and experiences which are systematically given to students to achieve goals. The curriculum is also an activity that includes various student activity plans in detail in the form of educational material forms, suggestions for teaching and learning strategies, program arrangements so that they can be implemented, and things that cover various activities until the desired goals are achieved. The Islamic Education Curriculum will not be separated from the principles of Islam itself, namely the Al-Qur'an and Al-Hadith, so the main characteristic that can be known is that it includes the Al-Qur'an and Al-Hadith as the main source. The Islamic education curriculum must emphasize religious and moral subjects. Religion and morals must be taken from the Al-Qur'an and Al-Hadith as well as examples from previous pious figures.